The Immigration Policies in Comparison (IMPIC) Dataset: Technical Report V2 - Valentin Berger; Liv Bjerre; Magdalena Breyer; Marc Helbling; Friederike Römer; Malisa Zobel (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2024)
The Immigration Policies in Comparison (IMPIC) database includes data on migration policies for 33 OECD countries and the period 1980-2018. The dataset is presented in Helbling, Marc, Liv Bjerre, Friederike Römer and Malisa Zobel (2016) "Measuring Immigration Policies: The IMPIC-Database", European Political Science 16 (1): 79-98. This technical report provides additional information on the data collection (part 1), the codebook of the dataset (part 2), a glossary that defines the relevant terms and concepts that have been used (part 3) and the questionnaire that has been used to collect the data (part 4). This second version of the technical report also includes information on the update of the dataset for the years 2011-2018.
Keywords: 300; immigration; policy; measurement; aggregation